Virulence genes and genetic relationship of L. monocytogenes isolated from human and food sources in Brazil - Almeida,Rosana Macedo de (2017)
ABSTRACT The herein presented assay provided a bacteriological and molecular characterization of 100 samples of L. monocytogenes isolated from human (43) and food (57) sources, from several regions of Brazil, and collected between 1975 and 2013. Antigenic characterization defined 49% of serotype 4b samples, followed by 28% of serotype 1/2b, 14% of serotype 1/2c, 8% of serotype 1/2a, and 1% of serotype 3b. Both type of samples from human and food origin express the same serotype distribution. Multiplex PCR analysis showed 13 strains of type 4b with the amplification profile 4b-VI (Variant I). Virulence genes hly, inlA, inlB, inlC, inlJ, actA, plcA, and prfA were detected in all samples, highlighting a deletion of 105pb on the actA gene in 23% of serotype 4b samples. Macrorestriction profile with ApaI at PFGE showed 55 pulsotypes, with the occurrence of the same pulsotype in hospitalized patients in São Paulo in 1992 and 1997, and two other highly related pulsotypes in patients hospitalized in Rio de Janeiro in 2008. Recognized pulsotypes in listeriosis cases have also been detected in food. Thus, the prevalence of a serotype and the persistence of certain pulsotypes herald future problems.